The influence of green product and process innovation on new product success: the mediating role of green product competitive advantage - Cheong, Kit Mun (2017)
Many firms including the small and medium enterprises (SMEs) in the plastic industry adopt innovative strategies to meet the green requirement. These firms not only generate better sales revenue and market share but also ensure success in their new green products. Developing green innovation not only meets the environmental regulations but also builds up barriers to other competitors, enhances their production efficiency which contributes to success. This study investigated the effects of green product innovation and green process innovation on green new product success of manufacturing SMEs in the plastic industry in Malaysia. The study also examined the mediating role of green product competitive advantage on the relationship between green product innovation and green new product success, and on the relationship between green process innovation and green new product success. Data were collected from the SME plastic manufacturers registered with the Malaysian Plastic Manufacturers Association and the systematic random sampling was employed in selecting them. A total of 300 self-reported questionnaires were emailed to the respondents and 207 were returned, giving a response rate of 69 percent. However, only 191 responses were usable for the final analysis. Findings revealed that green product innovation and green process innovation were positively and significantly related to green new product success. Further analysis indicated that green product competitive advantage partially mediated the relationship between green product innovation, green process innovation, and green new product success. The findings of this study contribute mainly to the current literature on green innovation especially in the Malaysian context where similar studies are generally scarce. Moreover the study specifies a strategy on how to improve the green new product success among SMEs in the plastic industry. The study concluded with a discussion of the theoretical, practical implications, the limitations and suggestions for future research.